UTILIZATION OF THE PDRI MUSEUM AS A LEARNING RESOURCE IN LEARNING HISTORY AT STATE SENIOR HIGH SCHOOL 1 GUNUANG OMEH DISTRICT - Yulian Gusmita; Bunari; Asyrul Fikri (SOSIOEDUKASI, 2026)
One of the efforts to use the surrounding environment as a learning resource is to make the PDRI Museum a learning resource in learning history. The history teacher of SMA Negeri 1 Gunuang Omeh District used the location as a contextual learning resource for students. This research aims to: (1) find out the use of the PDRI Museum as a learning resource in history learning at SMA Negeri 1 Gunuang Omeh District. (2) To find out the obstacles faced by teachers and students in utilizing the PDRI Museum as a learning resource in learning history at SMA Negeri 1 Gunuang Omeh District. (3) To find out the impact of the use of the PDRI Museum as a learning resource in history learning at SMA Negeri 1 Gunuang Omeh District. The research method used in this study is a qualitative method that aims to describe the use of the PDRI Museum as a learning resource in history learning for students at SMA Negeri 1 Gunung Omeh District. Data collection techniques are carried out through observation, interviews, and documentation studies. Data analysis uses the stages of data reduction, data presentation, and conclusion drawn. In its implementation, the history teacher of SMA Negeri 1 Gunuang Omeh District uses the PDRI Museum as a learning resource through the field trip learning model. Although there are a number of obstacles faced during the process of using the museum, the application of this field trip model has proven to have a positive impact, both on improving the quality of history learning and on the growth of students' appreciative attitude towards local history.